Exploring the silage quality of alfalfa ensiled with the residues of astragalus and hawthorn. (February 2020) - Ni, Kuikui; Wang, Xuekai; Lu, Yin; Guo, Linna; Li, Xiaomei; Yang, Fuyu
Highlights: Effect of addition of herb residue on silage quality was examined. AS and HN could reduce the contents of butyric acid and NH3 -N. Growth of Clostridium, Enterobacter and fungi was inhibited by the addition of AS and HN. The efficiency of AS and HN for inhibiting Clostridium, Enterobacter and fungi differed. Abstract: This study evaluated the effect of astragalus (AS) and hawthorn (HN) residues on the silage quality of alfalfa. Alfalfa was ensiled with additives (AS, HN and AS + HN) or without additives for 60 days. Results showed that the silage treated with AS and HN had lower contents of butyric acid and NH3 -N compared with control, whereas no significant differences of pH and lactic or acetic acid content were found. Additionally, the treated silages also exhibited lower copy numbers of Clostridium, Enterobacter and fungi during ensiling process established by qPCR. In conclusion, AS and HN could be used as additives to control the growth of unfavorable microorganism and enhance the silage quality.